Uso de aeronave remotamente pilotada para pulverização agrícola em diferentes condições operacionais - Lopes, Luana de Lima (2024)
The use of new technologies in agriculture that can offer greater flexibility in the field without losing efficiency is of great importance. One of these recent technologies that have emerged are remotely piloted aircraft (RPAs). However, research is still necessary in order to understand the dynamics of this equipment. Therefore, the present work aimed to evaluate the quality of the application with RPA in soybean and corn crops and in the application of glyphosate to control Urochloa decumbens using different spray nozzles, totaling three experiments. Each trial had four treatments and eight replications. In the soybean crop, the treatments consisted of aerial application (RPA, 10 L ha-1) with the XR 11001, AirMix 11001 and COAP 9001 nozzles. For comparison purposes, ground application was carried out via a backpack sprayer pressurized with CO2 (100 L ha-1) with the XR 110015 nozzle. In applications in corn crop and glyphosate for the control of Urochloa decumbens, the treatments were different application methods, aerial (RPA, 10 L ha-1) and ground (pressurized knapsack sprayer with CO2, 100 L ha-1), and the XR 11001 and AirMix 11001 nozzles. The deposition was evaluated, quantified using a spectrophotometric tracer, and the droplet spectrum, through the analysis of the water-sensitive paper, and the quality of the application was studied using the Statistical Process Control methodology. Furthermore, the effectiveness in control was evaluated, based on visual measurement with a percentage score, in the area of application of the herbicide for the control of Urochloa decumbens. Given the results obtained, it can be pointed out that the application via RPA presented itself as an appropriate technology within the conditions studied. In deposition, RPA stood out, but in terms of coverage and droplet density, the ground application performed better. For all applications, the deposition process presented quality from a statstical point of view. The AirMix nozzle stood out in terms of deposition and the lowest percentage of droplets smaller than 100 μm. At 21 days after applications, Urochloa decumbens control was above 84% in all treatments.